2016
DOI: 10.1177/0011392116663807
|View full text |Cite
|
Sign up to set email alerts
|

The visibility of scientific misconduct: A review of the literature on retracted journal articles

Abstract: Retractions of scientific articles are becoming the most relevant institution for making sense of scientific misconduct. An increasing number of retracted articles, mainly attributed to misconduct, is currently providing a new empirical basis for research about scientific misconduct. This article reviews the relevant research literature from an interdisciplinary context. Furthermore, the results from these studies are contextualized sociologically by asking how scientific misconduct is made visible through ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 134 publications
(253 reference statements)
2
78
0
1
Order By: Relevance
“…In the last two decades, the number of retractions has risen at a rate far exceeding the growth in the total number of published articles (see review in Hesselmann et al, 2017). Grieneisen and Zhang (2012) showed that "The number of articles retracted per year increased by a factor of 19.06 from 2001 to 2010," (Grieneisen & Zhang, 2012, p. 1).…”
Section: Retractionsmentioning
confidence: 99%
“…In the last two decades, the number of retractions has risen at a rate far exceeding the growth in the total number of published articles (see review in Hesselmann et al, 2017). Grieneisen and Zhang (2012) showed that "The number of articles retracted per year increased by a factor of 19.06 from 2001 to 2010," (Grieneisen & Zhang, 2012, p. 1).…”
Section: Retractionsmentioning
confidence: 99%
“…Evidence provided by recent studies indicates that retraction notices engage multiple parties [20]. In their lengthy discussion, M. L. Grieneisen and M. Zhang [4]; and B. K. Redman, H. N. Yarandi, and Jon F. Merz [26] underline that a good number of authorities usually constituted the source of retractions (i.e., authors, editors, peer-reviewers, and publishers) [4] [26].…”
Section: A Random Reasonsmentioning
confidence: 99%
“…John Bohannon's case indicates that reviewing any paper or the acceptance of a number of papers can happen mistakenly due to negative decisions made by reviewers or open access journals/publishers [30]. Andrew B. Rosenkrantz [8] and Felicitas Hesselmann [20] contend that retraction may be found in ambiguous words categorized in inadvertent or deliberate acts [8], [20]. In a study conducted by M. L. Grieneisen and M. Zhang [4], errors on retraction have been classified as random reasons appertaining to a number of factors such as authors and publishers along with unspecified ones, including honest errors, misconduct, and all sorts of fraud practices [4].…”
Section: A Random Reasonsmentioning
confidence: 99%
See 2 more Smart Citations